Multiple Inverters Operated in Parallel for Proportional Load Sharing in Microgrid - Chethan Raj D; D N Gaonkar (Institute of Advanced Engineering and Science, 2017)
The new energy source utilization and development, gradual rise of distributed power grid miniaturization, intelligence, control has become a trend. In order to make microgrid reliable and efficiently run, control technology of microgrid has become a top priority and an inverter as microgrid basic unit, its control has become the most important part in microgrid. In this paper, three inverters are operated in parallel using an P-V/Q-F droop control is investigated. Mathematical model of three phase inverter with LC filter is derived, which is based on the voltage and current dual control loop. Parallel control strategy based on P-V/Q-F droop control, does not require a real time communications between the inverters and more suitable for microgrid applications. To verify the feasibility and validity of the droop control scheme, simulation is done in Matlab/Simulink and results indicate droop control has significant effect on power sharing and balancing the voltage magnitude, frequency.